Magnetic ordering caused by a disorder in quasi-one-dimensional spin systems and non-Fermi-liquid systems - Zvyagin, A.A.; Makarova, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
In this Letter we show that a strong disorder in the distribution of exchange couplings betweenmagnetic impurities and hosts in quantum spin chains and non-Fermi-liquid rare earth and actinidecompounds can be the reason for magnetic orderings in these systems at low temperatures.